Millennials, FOMO, and the Qur’an: A Spiritual Response to a Modern Anxiety - Agustini; Sultan Gholand Astapala (JOURNAL OF QUR'AN AND HADITH STUDIES, 2025)
This study examines how the culture of Fear of Missing Out (FOMO) influences the tendency of millennials to become addicted to social media. As the number of internet users in Indonesia increases, especially among millennials, social media addiction has become a problem that negatively impacts the anxiety and mental health of this generation. The leading cause of growing anxiety and weakening self-confidence in social media addiction situations is FOMO, which is triggered by seeing other people's lives on social media. This article outlines at least four strategies for developing positive social media habits, including prioritizing yourself, avoiding excessive use, seeking genuine connections, and increasing self-esteem. It is hoped that these steps will help millennials overcome the negative impacts of social media addiction and FOMO, and create a positive social media culture based on the ideals of the Qur'an. This study tells us all about the importance of understanding the negative impacts of social media addiction, especially in the context of FOMO culture, and the need to change behavior to maintain mental health and balance in the lives of the younger generation.